ANALISIS EFEKTIVITAS SALURAN DISTRIBUSI GAS ELPIJI BERSUBSIDI DI KAWASAN KECAMATAN TAMAN SARI ( STUDY KASUS PT. USAHA MULIA KARYA MANDIRI PANGKALPINANG ) - Listianty, Fergy; Harjono; Medinal (Jurnal Progresif Manajemen Bisnis, 2018)
LPG (Liquid Petroleum Gas) is one of the oil and gas commodities produced by PT Pertamina (Persero). The government implements the national energy policy by converting kerosene to LPG. This is to minimize the kerosene subsidy which has the largest proportion of which is 50% of the government's energy subsidy and every year the subsidy grows. PT Pertamina (Persero) is releasing its product with a new packaging variant of 3 kg LPG, which is fully subsidized by the government so that kerosene consumers can switch to LPG. With the enactment of the conversion policy, all kerosene agents have become agents of 3kg LPG PT. Usaha Mulia Karya Mandiri is a company engaged in the field of gas distribution for gas size 3kg. PT. Usaha Mulia Karya Mandiri distributes its products in several areas in Pangkalpinang. In marketing its products, the company needs a marketing system that is the distribution channel that must be studied, so that the company can gain a wide advantage in some areas in the Pangkalpinang area. Related to the objectives to be achieved, namely the efficiency and effectiveness of the company and the use of existing resources. Increasingly tight market competition for its products can be widely spread to several areas in the Pangkalpinang area.